Makna Konotatif dalam Antologi Puisi Rubaiyat Den Sastro Karya Sapardi Djoko Damono - Husnul Hotimah; Desty Endrawati Subroto; Mahpudoh Mahpudoh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the connotative meanings found in the poetry anthology Rubaiyat Den Sastro by Sapardi Djoko Damono based on Geoffrey Leech's theory of connotative meaning. This study employed a descriptive qualitative method with a semantic approach. The primary data source was the poetry anthology Rubaiyat Den Sastro, while the research data consisted of words and phrases containing connotative meanings. Data were collected through reading and note-taking techniques. The analysis of connotative meaning was based on Geoffrey Leech's theory, while the data analysis employed the model proposed by Miles, Huberman, and Saldana, which consists of data condensation, data display, and conclusion drawing and verification. The findings show that 44 data containing connotative meanings were identified. Of these data, seven were selected for further analysis in this article. The connotative meanings identified emerged through the use of words and phrases that convey meanings beyond their conceptual meanings and are shaped by their context of use in the poems. The analysis shows that connotative meaning can be understood by examining the differences between conceptual meaning and the meaning that emerges from the context in which words or phrases are used within individual lines and the poems as a whole.